Comparison Between two Different Doses of Ketamine as Pre-Emptive Analgesic in Patients of Laparoscopic Cholecystectomy for Postoperative Analgesia - Divecha, Nikita P.; Patel, Dhaval Kumar C (Academia Anesthesiologica International, 2022)
Background: Pre-emptive analgesic can be used as to decrease early pain post-surgery and also prevent the formation of long-term pain by subsiding the CNS sensory pathway. Ketamine is an n-methyl-d-aspartate (NMDA) receptor antagonist, desired for its effectiveness to intercept intraoperative as well as postoperative pain as a pre-emptive analgesic. Ketamine blocks the NMDA receptors and obliterate the peripheral painful stimulation and theory shows it prevents CNS stimulation. Following lap cholecystectomy pain comes from various components like peritoneal stretching, diaphragmatic irritation and insufflation. So, the study was planned to assess pre-emptive analgesic efficacy of ketamine for patients posted for lap cholecystectomy. Subjects and Methods: Randomly patients were allocated in 3 groups of thirty patients with ASA grade I and II of either sex, age group between 18 to 55 years admitted for laparoscopic cholecystectomy. After preoxygenation patient induced and intubated with proper size endotracheal tube. Post intubation the study drug was diluted upto10ml with saline and administered i.v by an anaesthesiologist 10 minutes before skin incision. Group A patients received Inj.Ketamine 0.5mg/kg i.v, Group B patients received Inj.Ketamine 1.0mg/kg i.v, Group C patients received Normal Saline i.v. This study was carried out to compare and evaluate the efficacy of different doses of ketamine (0.5 and 1.0 mg/kg IV) for pre-emptive analgesia in patients of laparoscopic cholecystectomy with reference to Intraoperative hemodynamic changes, VAS score, time for first top-up analgesic, total number of doses of analgesic used within first 12 hours, postoperative hemodynamic changes, adverse effects. Results: The demographic profile and the period of sedation/operation was found to be comparable in groups. Pulse rate and systolic Bp was slightly high in ketamine Group (1.0mg/kg) as compared to ketamine Group (0.5mg/kg) and Group C in first 20 mins which was statistically significant. After 20 minutes pulse rate and systolic Bp higher in saline Group compared to ketamine Groups which was statistically significant. The mean VAS score on deep breathing, at rest and on movement was significantly higher in saline group as compared to ketamine groups postoperatively. The average time for initial rescue analgesic was significantly higher in ketamine groups (1mg/kg & 0.5mg/kg) on average 3 hours as compared to saline group less than hour. Adverse effects related to ketamine was found to be higher with 1.0mg/kg as compared to 0.5mg/kg and saline. Conclusion: Hence, ketamine has a conclusive role as a pre-emptive analgesic in minimizing postoperative pain. It also decreases requirement of analgesic in patients undergoing laparoscopic cholecystectomy. Lower dose of ketamine with 0.5mg/kg having fewer side effects and with less vital parameter changes is an ideal dose as pre-emptive analgesia.